Effect of Volcanic Activity on Hydrocarbon-Forming Organisms in Organic-Rich Shale: A Case Study of Dalong Formation in Northwestern Sichuan Basin, China - Zhang, Chuanwen; Meng, Qingqiang; Tang, Xuan; Sun, Zuoyu; Pang, Qian; Lyu, Dawei; Zhu, Dongya; Liu, Jiayi; Li, Jiachun; Jiang, Bin (Frontiers in Earth Science, 2022)
Hydrocarbon-generating material determines the elemental composition and hydrocarbon-generating potential of kerogens in a source rock, and it is the key material basis to control the hydrocarbon-generating capacity of the source rock. Previous studies have shown that many intervals of high-quality source rocks generally contain a varying number of volcanic ash layers. The impact of these volcanic ash layers on the development of high-quality source rocks has attracted extensive attention. However, these studies mainly focused on the development of hydrocarbon-forming organisms and the preservation of organic matters but rarely dealt with the differential development of hydrocarbon-forming organisms between multiple volcanic ash layers. The Permian Dalong Formation in the northwestern Sichuan Basin, China, is a set of high-quality source rocks with multiple volcanic sedimentary layers. To understand the differential development of hydrocarbon-forming organisms between volcanic ash layers, with the Dalong Formation in the Longfeng quarry section, Guangyuan, the Sichuan Basin as an example, this study analyzes the types of hydrocarbon-generating materials of high-quality source rocks of the Dalong Formation and the reasons why volcanic activities affected the growth of hydrocarbon-forming organisms and explores the impact of volcanic activities on the development of different types of hydrocarbon-forming organisms. The results show that the TOC of the Longfeng quarry section is 0.05%–15.46%, with an average of 4.76%, and the average TOC of the Dalong Formation is as high as 5.16%, which belongs to high-quality source rocks. The hydrocarbon-forming organism association in the Dalong Formation source rocks is mainly composed of floating algae and benthic algae and vertically divided into three parts: a few radiolarians and trace fossils occasionally in the lower part; a large number of radiolarians, calcium spheres, and algal debris in the middle part; and mainly foraminifera and gastropods in the upper part. There are 36 volcanic ash layers in the Dalong Formation of the study area. In the process of volcanic activity, the “fertilization” effect of volcanic ash made the nutrient elements in the volcanic ash enter water, increasing the number of hydrocarbon-forming organisms, causing the differential development of various hydrocarbon-forming organisms, and promoting the formation of reducing water to support the preservation of organic matters. The development of hydrocarbon-forming organisms is controlled by the changes of element types and abundances caused by magmatic properties. The time interval of volcanic activities also has an important impact on the development of hydrocarbon-forming organisms.